World book 2001 Vol. 13 M / Mary Alice Anderson - Anderson, Mary Alice (Estados Unidos de América: World book, Inc, 2001)
Additional resources, early life, early public career, impotent events during MacDonald's administrations, second term as prime minister, principles of machine, how machines change the direction of motion, six simple machines, designing machines, basic machine tool operations advanced machine tool operations, numerical control of machine tools, history, entry into political life, prime minister, later years additional resources.
Portada ilustrada, mapa, cuadro
Col. Enc
Keywords: 1. ENCICLOPEDIA 2. WORLD BOOK M VOL. 13 3 REFERENCIA